Single-dose rofecoxib for acute postoperative pain in adults: a quantitative systematic review - McQuay Henry J; Edwards Jayne E; Barden Jodie; Moore R Andrew (BMC Anesthesiology, 2002)
Abstract Background Rofecoxib is a cyclo-oxygenase 2 selective inhibitor. This systematic review of rofecoxib in acute pain examined studies in adults of analgesic efficacy over six hours, the amount and quality of the evidence on extended duration of analgesia, and the quality and quantity of evidence on adverse events. Methods Cochrane Library (issue 4, 2001), Biological Abstracts (March 2002), MEDLINE (March 2002) and PubMed (March 2002) were searched using rofecoxib as a free text term. The area under the pain relief versus time curve was dichotomized using validated equations to derive the proportion of patients on rofecoxib 50 mg or placebo with at least 50% pain relief over six hours. This was used to calculate the number needed to treat for at least 50% pain relief over six hours for rofecoxib compared with placebo. Information on duration of analgesia and adverse events was also collected. Results Five included trials investigated 1,118 patients, of whom 211 received placebo and 464 received rofecoxib 50 mg. The NNT for rofecoxib 50 mg was 2.3 (95% confidence interval 2.0 to 2.6). The weighted mean remedication time was 1.9 hours for placebo (126 patients), 7.4 hours for ibuprofen 400 mg (97 patients) and 13.6 hours for rofecoxib 50 mg (322 patients). Conclusion Rofecoxib at 2–4 times the standard daily dose for chronic pain is an effective single dose oral analgesic in acute pain. Limitations in trial reporting constrain conclusions about longer duration of analgesia and adverse event profile.